2019
DOI: 10.3390/met9030296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermomechanical Treatment on Acicular Ferrite Formation in Ti–Ca Deoxidized Low Carbon Steel

Abstract: Transformation behaviors and mechanical properties under thermomechanical treatment conditions of Ti–Ca deoxidized low carbon steel were studied in comparison to Al–Ca treated steel. A thermomechanical simulation and a hot rolling experiment were carried out. Inclusions and microstructures were characterized, and the transformation mechanism was analyzed. The results indicated that typical inclusions in Ti–Ca deoxidized steel were TiOx-MnS-Al2O3-CaO, TiOx-MnO-Al2O3-CaO, and TiOx-MnS, which were effective for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…content, which contributed to promoting AF nucleation [27]. In the present experimental steel, Ti oxide was the main inclusion type and was considered to be effective through the MDZ mechanism.…”
Section: As-cast Microstructure and Inclusionmentioning
confidence: 83%
See 1 more Smart Citation
“…content, which contributed to promoting AF nucleation [27]. In the present experimental steel, Ti oxide was the main inclusion type and was considered to be effective through the MDZ mechanism.…”
Section: As-cast Microstructure and Inclusionmentioning
confidence: 83%
“…The formation of MDZ caused a decrease in Mn content and an increase in transformation temperature, which promoted intragranular AF nucleation around the inclusion [25,26]. In addition, the driving force for ferrite formation, i.e., the Gibbs free energy change for γ→α, increased with a decrease in Mn content, which contributed to promoting AF nucleation [27]. In the present experimental steel, Ti oxide was the main inclusion type and was considered to be effective through the MDZ mechanism.…”
Section: As-cast Microstructure and Inclusionmentioning
confidence: 99%
“…The hardness values from existing work in the field have been observed to respond to differences in heat inputs, and consequently, cooling rates by changes to the composition of the microstructures of WAAM fabricated steels. Wang et al found that Hv values appreciated with increasing cooling rate from of acicular ferrite forming at a lower temperature with dislocation density increasing [37]. Yildiz also commented on the changes from low to high heat input with decreasing volume fraction of bainitic and martensitic microstructural components and replaced by acicular ferrite [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, for containing Ti–Ca or Ti–Ca–Al oxide particles, the aforementioned studies mainly focus on the evolution and characterization of inclusions. Although our team determined that Ti–Ca oxides can facilitate AF nucleation and enhance mechanical properties of steel base metal, the influence of different heat input on the toughness and microstructure of CGHAZ containing Ti–Ca or Ti–Ca–Al oxide particles has not been studied. The relationship between AF nucleation and CGHAZ toughness, with increased heat input, needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%